Evaluasi Kinerja Hutan Kemasyarakatan Merte Sari Desa Sengigi Kecamatan Batu Layar Kabupaten Lombok Barat - Ghozul Fikri, Muhammad; Markum, Markum; Setiawan, Budhy (Jurnal Pendidikan, Sains, Geologi, dan Geofisika (GeoScienceEd Journal), 2025)
This research evaluates the management performance of the Merte Sari Community Forest (HKm) in Sengigi Village, Batu Layar District, West Lombok Regency, with a focus on social aspects and supporting and inhibiting factors. Referring to the HKm evaluation guidelines in Perdirjen P.9/PSKL/PKPS/KUM.1/10/2019, this research found that Merte Sari's HKm management performance was in the good category with a score of 286, reflecting increased community welfare, institutional strengthening, behavioral changes management, and contribution to forest management. Supporting factors include good planning, member participation, institutional training, and women's involvement. However, inhibiting factors include a lack of biophysical data and NTFP potential, as well as suboptimal coordination and enforcement of regulations. This research suggests the need for forest product processing training, regular institutional development, institutional strengthening with the help of related parties, and further research on the potential for environmental services to support the development of the Merte Sari HKm. Interviews Interviews are a method of data collection where there is a question and answer interaction between researchers and respondents in this research, the approach used is based on the research objectives